GraphWare: A graph‐based middleware enabling multi‐robot cooperation. (4th April 2022) - Chen, Jinlin; Cao, Jiannong; Liang, Zhixuan; Cheng, Zhiqin; Wang, Jia
Summary: Multi‐robot systems are widely used to handle complex and cooperative missions in various industrial applications. Although robotic middleware has become the key to reducing the complexity of multi‐robot application development, existing works still have limitations in controlling multiple robots to perform missions cooperatively. To enable multi‐robot cooperation, middleware should provide high‐level abstraction support, dynamic configuration, communication, and synchronization. In this article, we propose GraphWare, a novel middleware that provides a graph‐based programming abstraction and its underlying runtime kernel for programming and building multi‐robot cooperation applications. The graph‐based programming abstraction can express cooperative missions without exposing the complexity of managing multiple robots. The runtime kernel configures and manages multiple heterogeneous robots to intelligently perform cooperative missions. We implement GraphWare and evaluate its performance with ball collection missions which are cooperatively accomplished by a group of mobile robots, and study the fault‐tolerance, flexibility, and scalability of the middleware in the realistic simulation. The experimental results demonstrate that GraphWare facilitates the multi‐robot cooperative mission with efficient mission completion time, high success rate, and marginal runtime overhead.